Proceedings of the 11th Working Conference on Mining Software Repositories 2014
DOI: 10.1145/2597073.2597082
|View full text |Cite
|
Sign up to set email alerts
|

Modern code reviews in open-source projects: which problems do they fix?

Abstract: Code review is the manual assessment of source code by humans, mainly intended to identify defects and quality problems. Modern Code Review (MCR), a lightweight variant of the code inspections investigated since the 1970s, prevails today both in industry and open-source software (OSS) systems. The objective of this paper is to increase our understanding of the practical benefits that the MCR process produces on reviewed source code. To that end, we empirically explore the problems fixed through MCR in OSS syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
150
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(166 citation statements)
references
References 44 publications
16
150
0
Order By: Relevance
“…Our interviews with developers indicated that creating short-lived micro-clones might be common in software development, but that the developers usually catch them early, or at least during their own or someone else's review of the code (Beller et al 2014). The cognitive error in the remaining micro-clones we observed in this study is thus not only a production error, but also a proofreading error (Healy 1980): During revision of the code, the engineer fails to notice the error in the last and other lines.…”
Section: Example 1 Trinitycorementioning
confidence: 97%
“…Our interviews with developers indicated that creating short-lived micro-clones might be common in software development, but that the developers usually catch them early, or at least during their own or someone else's review of the code (Beller et al 2014). The cognitive error in the remaining micro-clones we observed in this study is thus not only a production error, but also a proofreading error (Healy 1980): During revision of the code, the engineer fails to notice the error in the last and other lines.…”
Section: Example 1 Trinitycorementioning
confidence: 97%
“…The role of the reviewer assigner is important in order to efficiently perform the code review process [7]. If a reviewer assigner assigns an unsuitable reviewer who does not deeply understand the given source code change, the author of the source code change may obtain poor review outcomes.…”
Section: Code Review Processmentioning
confidence: 99%
“…Inefficient logic and latent bugs in the source code significantly increase the maintenance costs of a software project. Although code reviews are time consuming, it is beneficial to detect the defects in the source code at an early software development stage [1,[3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracting knowledge from these datasets has produced promising research with the goal of improving the software quality and software development process. Recently, many studies have used code review datasets to understand and improve both review effort [2]- [5] and review quality [6], [7]. However, a raw code review dataset is generally imperfect since the data collection process in each support tool 1 https://code.google.com/p/gerrit/ 2 https://www.reviewboard.org/ 3 https://code.google.com/p/rietveld/ varies in methodology, accuracy, and degree of automation [8].…”
Section: Introductionmentioning
confidence: 99%